Mineral deficiencies and excess in the bean plant (Phaseolus vulgaris L. var. carioca) - Malavolta, E.; Damião Filho, C.F.; Volpe, C.A.; Machado Jr., C.R.; Velho, L.M.S.; Rosa, P.R.F.; Laurentiz, S. de (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1980)
This work had the purpose of studying some aspects of the mineral nutrition of the bean plant (Phaseolus vulgaris L., var. Carioca) checking the effects of the ommission of macronutrients and also B and Fe and the excesses of Al and Mn. Some changes in heigth of the plants and the number of leaves, yield of dry matter and mineral composition of leaves and roots were observed. To check the effects of ommission of N, P, K, Ca, Mg, S, Fe and B, and excesses of Mn and Al, bean plants were grown in controlled conditions. The harvest was done when the induced symptoms were well established. From the obtained data, it is concluded that: 1. Ca was the element that, when missing, had the major depressive effect on heigth of the plants, number of leaves, and dry matter weight. 2. It is possible to induce symptoms of mineral deficiencies, and excesses in the bean plant if it is grown in the nutrient solution in the absence or excess of some elements. 3. Dry matter production was affected by treatments in the following increasing order: complete, - S, - K, + Al, -B, + Mn. - Mg, - Fe, - P, - N and - Ca. 4. The main interactions among the leaf elements, detected through this trial were: K x Ca x Mg, Fe x Mn. 5. The absence of an elements causes a decrease of its content in the leaves, when compared to the complete treatment.